Effects of combining cold exposure and compression on muscle recovery: a randomized crossover study - Millour, G.; Lepers, R.; Coste, A.; Hausswirth, C. (Frontiers in Physiology, 2025)
IntroductionThe study aimed to evaluate the effects of combining lower-limb cold exposure and intermittent compression on optimizing post-exercise recovery.MethodsFifteen male recreational athletes were recruited for a randomized crossover study comparing two recovery strategies: cryocompression and passive recovery, both applied in a supine position for 30 min. These interventions followed a high-intensity plyometric exercise and were repeated over the subsequent 2 days. Performance metrics included counter movement jumps and squat jumps, 30-s Wingate cycling test, maximal voluntary contraction (MVC) force of knee extensors, prolonged low-frequency force depression (PLFFD), inflammatory markers, and subjective assessments of muscle soreness and heaviness. Measurements were taken at four time points: pre-exercise, immediately post-recovery, 24 h post, and 48 h post.ResultsCryocompression significantly accelerated muscle recovery by reducing PLFFD and inflammation markers (salivary interleukin-1 beta and thigh circumference), while enhancing performance during MVC. Furthermore, perceived lower-limb heaviness, muscle soreness, and body pain decreased more rapidly with cryocompression at 24- and 48-h post-recovery. However, no significant differences were observed between the recovery strategies in cycling or jumping performance.DiscussionThese findings underscore cryocompression as a promising recovery strategy for athletes seeking to mitigate exercise-induced muscle damage and restore performance. Further research is warranted to investigate the applicability of these results across diverse athletic populations.